Reclaiming China’s former soft power - Keane, Michael (The Oriental Society of Australia, 2010)
The discussion begins with a discussion of soft power and creativity in contemporary China. The article then examines three development trajectories: territory, technology and taste. The third section examines the effects of taste in more detail through examples of China’s creativity in art, philosophy and technology primarily in three key periods, the Western Zhou, Han, and Song The principal argument is that while China’s cultural authority was established on deep Confucian roots, its international influence, and its creativity, is indebted to periods of openness to ideas.